2020
DOI: 10.15655/mw/2020/v11i3/202929
|View full text |Cite
|
Sign up to set email alerts
|

National Policy and the Media in the Formation of Environmental Awareness among Students of Kazakhstan

Abstract: The relevance of the study is determined by the question as to in which version the environmental consciousness of a person should be considered. The novelty of the study is determined by the possibility of not only forming ecological awareness but also imparting environmental education in their professional and everyday living environments. The authors consider the aspect of structuring the teaching of ecological knowledge of students as the most active layer of the population. It is shown that the possibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…In terms of research progress in environmental awareness studies, there are numerous research articles published on this particular topic in the context of Kazakhstan. For instance, these included studies done by Zhurtbay [93] and Tursynbayeva et al [94] on the inter-related aspects of how the media and national policy form environmental awareness elements among different groups of the population in the country. Another group of scholars approached it from the context of ecological education and how the process of pedagogical teaching affected the level of awareness among different groups young people [95][96][97][98][99][100], while other researchers looked at the degree of awareness levels for various environmental problems ranging from the role of NGOs and civic society organizations [101][102][103][104][105], and from the point of view of access to environmental information to the public community [106].…”
Section: Research Progress In Kazakhstanmentioning
confidence: 99%
“…In terms of research progress in environmental awareness studies, there are numerous research articles published on this particular topic in the context of Kazakhstan. For instance, these included studies done by Zhurtbay [93] and Tursynbayeva et al [94] on the inter-related aspects of how the media and national policy form environmental awareness elements among different groups of the population in the country. Another group of scholars approached it from the context of ecological education and how the process of pedagogical teaching affected the level of awareness among different groups young people [95][96][97][98][99][100], while other researchers looked at the degree of awareness levels for various environmental problems ranging from the role of NGOs and civic society organizations [101][102][103][104][105], and from the point of view of access to environmental information to the public community [106].…”
Section: Research Progress In Kazakhstanmentioning
confidence: 99%
“…Συνεπώς η εκπαίδευση, ως μέσο που μπορεί να συμβάλει σημαντικά στην καλλιέργεια ΠΥΣ, μπορεί να αξιοποιηθεί στα πλαίσια μιας ενιαίας συνολικής κρατικής πολιτικής, αλλά και από επιχειρήσεις που θέλουν να υιοθετήσουν ΠΥΣ (Vicente-Molina et al, 2013). Αυτό ενισχύεται και από την τοποθέτηση των Tursynbayeva et al, (2020) οι οποίοι υποστηρίζουν πως η περιβαλλοντική εκπαίδευση εκτός από το πανεπιστήμιο, πρέπει να εμβολιάζει όλες τις πτυχές της καθημερινότητας των ανθρώπων συμπεριλαμβανομένου και του εργασιακού χώρου.…”
Section: εισαγωγήunclassified
“…The authors in their study argue that it is opportune to revisit profound questions about the purpose, nature, and value of higher education in society at a juncture where the context of higher education has been significantly influenced by the global sustainability agenda and responsible management education imperatives (Cicmil et al, 2017). In turn, it is difficult to disagree with the conclusion of Gao (2015), which, while studying the "Education for International Understanding" (EIU) program, has become popular in East Asia found that the current curriculum of EIU needs to not only embed factual knowledge but also needs to present the roots and reasoning behind that knowledge for students (Tursynbayeva et al, 2020). We should also be aware that democracy encourages contributions from different voices.…”
Section: Introductionmentioning
confidence: 99%